Therapeutic strategies in the treatment of periodontitis - Liljana Bogdanovska; Silvana Kukeska; Mirjana Popovska; Rumenka Petkovska; Katerina Goracinova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
Periodontitis is a chronic inflammatory process which affects the tooth - supporting structures of the teeth. The disease is initiated by subgingival periopathogenic bacteria in susceptible periodontal sites. The host immune response towards periodontal pathogens helps to sustain periodontal disease and eventual alveolar bone loss. Although scaling and root planing is the standard treatment modality for periodontitis, it suffers from several drawbacks such as the inability to reach the base of deep pockets and doesn't arrest migration of periodontal pathogens from other sites in the oral cavity. In order to overcome the limitations of scaling and root planning, adjunctive chemotherapeutics and host modulatory agents to the treatment are used. These therapeutic agents show substantial beneficial effects when compared to scaling and root planning alone. This review will cover an update on chemotherapeutic and past and future host immune modulatory agents used adjunctively to treat and manage periodontal diseases.